Staining of activated ß2-integrins in combination with CD137 and CD154 for sensitive identification of functional antigen-specific CD4+ and CD8+ T cells - Schöllhorn, Anna; Maia, Ana; Kimmerle, Felix; Born, Jan; Rammensee, Hans-Georg; Dimitrov, Stoyan; Gouttefangeas, Cécile (Frontiers in Immunology, 2023)
Common flow cytometry-based methods used for functional assessment of antigen-specific T cells rely on de novo expression of intracellular cytokines or cell surface activation induced markers. They come with some limitations such as complex experimental setting, loss of cell viability and often high unspecific background which impairs assay sensitivity. We have previously shown that staining of activated ß2-integrins either with multimers of their ligand ICAM-1 or with a monoclonal antibody can serve as a functional marker detectable on T cells after minutes (CD8+) or few hours (CD4+) of activation. Here, we present a simple method for detection of activated ß2-integrins in combination with established cell surface activation induced markers. We observed that activated ß2-integrins were still detectable after 14 hours of stimulation, allowing their detection together with CD137 and CD154. Combinatorial gating of cells expressing activated ß2-integrins and CD137 or CD154 reduced background in unstimulated samples, increasing the signal-to-noise ratio and allowing improved assessment of low-frequency T cell responses. Extracellular staining of these markers highly correlated with production of intracellular cytokines IL-2, TNF or IFN-γ in CD4+ and CD8+ T cells. As an exemplary application, SARS-CoV-2 spike-specific T cell responses were assessed in individuals after COVID-19 vaccination. This method should be useful for epitope discovery projects and for the simultaneous monitoring of low-frequency antigen-specific CD4+ and CD8+ T cell responses in various physiological situations.